Método para classificação da reação de genótipos de cana-de-açúcar às ferrugens marrom e alaranjada - Lima, Wéllima Timóteo de (Universidade Federal de São Carlos, 2021)
The brown and orange rusts of sugarcane are diseases of concern to the sugarcane industry, due to the rapid spread of causal agents and the potential for damage to productivity. The main method for controlling both is the planting of resistant varieties, which is why genetic improvement programs must conduct tests that determine, with assertiveness, the reaction of genotypes to these diseases. The objective of this work was to establish a method to classify the reaction of sugarcane genotypes to brown and orange rust, based on field experiments under natural infection conditions. Between 2015 and 2019, five experiments were conducted in the city of Araras, São Paulo. The varieties SP89-1115 and RB835486, susceptible to orange rust and brown rust, respectively, were used as infective lines, with the objective of increasing and uniforming the inoculum pressure on the genotypes to be evaluated. The eight varieties selected for this work were compared to each other through the variables maximum severity score and area under the corrected disease progress curve (AACPDC). Subsequently, the AACPDC relative to the standard susceptibility varieties was calculated in order to classify the genotypes as resistant, intermediate or susceptible to each rust. Considering brown rust, varieties RB855156, RB92579, SP81-3250 and SP89-1115 were resistant, while CTC4 and RB855035 were susceptible, and SP80-1842 was intermediate. Regarding orange rust, the genotypes CTC4, RB835486, SP80-1842 and RB855035 showed resistance, while the varieties RB855156 and RB92579 showed an intermediate reaction and SP81-3250 was classified as susceptible. The method used to classify the reaction of sugarcane genotypes to rust is suitable for experiments conducted under conditions similar to those of the present study, as it was able to differentiate the evaluated varieties into resistant, intermediate and susceptible to both diseases.
Method for classifying the reaction of sugarcane genotypes to brown and orange rust
Keywords: Saccharum spp; Puccinia melanocephala; Puccinia kuehnii; Severidade; Controle genético; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA::MELHORAMENTO VEGETAL